Urban public transport deregulation: The Chilean experience - Baytelman, Yael; Paredes, Ricardo (Estudios de Economía, 2016)
Over the last fifteen years, urban transport congestion in Santiago, Chile has concerned authorities, academicians and the public in general. Unlike other congested cities, the case of Santiago is a very special one, since it makes it possible to compare different regulatory mechanisms within the same institutional context and within the same city. After facing a very poor transport system, both in coverage and frequencies, the deregulation of the sector in 1979 was a blessing for those needed public transportation. However, massive entry into the industry occurred. Entry created congestion and fares did not fall, instead they dramatically increased due to the existence of a collusive cartel despite free entry of firms. The cause of the Chilean cartel was not, as in other cases, a high supply concentration in the industry, but rather the lack of clarity in both the regulator and the Antitrust Commissions, which gave too much power to bus owner associations. Another lesson to be learned from the Chilean experience is that reducing entry does not necessarily imply increasing monopoly rents. This tradeoff can be reduced through competitive tendering.